2020
DOI: 10.1101/2020.06.03.20121525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude and kinetics of anti-SARS-CoV-2 antibody responses and their relationship to disease severity

Abstract: Background: SARS-CoV-2 infection can be detected indirectly by measuring the host immune response. Anti-viral antibody concentrations generally correlate with host protection and viral neutralization, but in rare cases, antibodies can promote disease progression. Elucidation of the kinetics and magnitude of the SARS-CoV-2 antibody response is essential to understand the pathogenesis of COVID-19 and identify potential therapeutic targets. Methods: Sera (n=533) from patients with RT-PCR confirmed COVID-19 (n=15… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 23 publications
10
85
3
Order By: Relevance
“…Initial diagnosis had been confirmed by public health authorities through either PCR or epidemiologic contact. All participants also met the donor selection criteria for plasma donation in use at HĂ©ma- Consistent with previous reports on the rate of seroconversion of COVID-19 patients (16)(17)(18), the overall proportion of our convalescent plasma donors (n=282) that were tested seronegative at the time of donation was 6.9%. However, we noted that this proportion increased to about 15% if we considered only donors who had waited for more than 11-12 weeks after symptoms onset before donating ( Table 1).…”
Section: Main Textsupporting
confidence: 70%
“…Initial diagnosis had been confirmed by public health authorities through either PCR or epidemiologic contact. All participants also met the donor selection criteria for plasma donation in use at HĂ©ma- Consistent with previous reports on the rate of seroconversion of COVID-19 patients (16)(17)(18), the overall proportion of our convalescent plasma donors (n=282) that were tested seronegative at the time of donation was 6.9%. However, we noted that this proportion increased to about 15% if we considered only donors who had waited for more than 11-12 weeks after symptoms onset before donating ( Table 1).…”
Section: Main Textsupporting
confidence: 70%
“…In line with the expected sequential appearance of antibody isotypes, the majority of studies reported detection of IgM followed by IgG. 15,23,39,40 Nevertheless, this finding was not consistent across all studies. One study measured time to seroconversion for IgA, IgM, and IgG and demonstrated detection of IgA and IgM simultaneously, followed by IgG.…”
Section: Sequential Antibody Responsementioning
confidence: 84%
“…Most immunocompetent individuals with symptomatic infections develop detectable SARS-CoV-2 antibodies within 2 weeks of symptom onset. 1 The SARS-CoV-2 IgG antibody response is more robust in severe cases of COVID-19 at all time-points after seroconversion. 1 Preliminary findings suggest that the magnitude of the antibody response correlates with virus neutralizing power, but some hypothesize that the antibodies could promote disease progression.…”
Section: Main Textmentioning
confidence: 90%
“…1 The SARS-CoV-2 IgG antibody response is more robust in severe cases of COVID-19 at all time-points after seroconversion. 1 Preliminary findings suggest that the magnitude of the antibody response correlates with virus neutralizing power, but some hypothesize that the antibodies could promote disease progression. 2 Influential factors in the distinction between protective antibodies and those that promote pathology include antibody isotype, concentration, specificity, post-translational modifications, and avidity for the virus.…”
Section: Main Textmentioning
confidence: 90%